Adsorptive recovery of Au(III) from aqueous solution using crosslinked polyethyleneimine resins. (February 2020) - Liu, Fenglei; Zhou, Liang; Wang, Wenjing; Yu, Gang; Deng, Shubo
Abstract: Resin adsorption is considered as a promising method to recover gold ions from wastewater, but further reduction reaction is required to convert gold ions into particles. In this study, a crosslinked polyethyleneimine resin (CPEIR) was developed via a suspension polymerization of polyethyleneimine (PEI) and ethylene glycol diglycidyl ether (EGDE) for gold recovery. The Au(III) adsorption capacities of CPEIR were significantly impacted by solution pH and initial Au(III) concentrations but unaffected by co-existing metal ions. Compared with commercial anion-exchange resin IRA400, the CPEIR exhibited higher sorption amount and selectivity for Au(III) due to its high density of amine and hydroxyl groups on the surfaces. The adsorption isotherm of Au(III) on CPEIR was well described by the Langmuir equation, and the maximum uptake amount of Au(III) was high up to 943.5 mg/g, much higher than the reported sorbents. The adsorption kinetic data on the CPEIR were fitted well by the Pseudo-second-order equation, and the intraparticle diffusion was found to be the rate-controlling process of Au(III) adsorption. X-ray photoelectron spectroscopy (XPS) and X-ray diffraction (XRD) analysis confirmed that Au(III) ions were adsorbed on the CPEIR via electrostatic attraction and chelating interaction, and subsequently the partial loaded Au(III) ions were reduced to elemental gold whereas the hydroxyl groups of CPEIR were oxidized to carbonyl groups. Graphical abstract: Image 1 Highlights: A crosslinked polyethyleneimine resin (CPEIR) was successfully prepared. The CPEIR exhibited high adsorption capacity of 943.5 mg/g for Au(III). Au(III) ions were adsorbed on CPEIR via electrostatic and chelating interactions. Partial loaded Au(III) ions were reduced to elemental gold on the CPEIR.